PENGARUH ASAP CAIR TEMPURUNG KELAPA TERHADAP DAYA AWET BAKSO IKAN - NURJAYA NURJAYA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to: 1) determine the effect of the concentration of coconut shell liquid smoke on the shelf life of fish balls, 2) determine the effect of storage time for fish balls on the durability of fish balls. The method used in this research is an experimental method with a completely randomized design (CRD) with a factorial pattern, each with 4 replications, so that the total treatment is 100 units. The independent variables in this study were the concentration of coconut shell liquid smoke which consisted of: control, liquid smoke 1.33%, 2%, 2.67%, 3.33% and the storage time of fish balls consisting of: control, 1 day, 2 days, 3 days, 4 days and the dependent variables in this study were phenol levels, pH, number of bacterial colonies and panelists' assessment. Data were analyzed by SPSS. The results showed that (1) the concentration of liquid smoke did not have a significant effect on phenol levels, pH, number of colonies, color, and texture of fish balls, (2) storage time had a significant effect on phenol levels, pH, number of bacterial colonies, color , aroma and taste of fish balls, (3) the results of organoleptic test research, assessment of color